ANALYSIS OF FINANCIAL AND NON-FINANCIAL FACTORS ON THE LEVEL OF UNDERPRICING IN COMPANIES CONDUCTING INITIAL PUBLIC OFFERING (IPO) ON THE INDONESIA STOCK EXCHANGE IN THE PERIOD 2018-2023 - Arsinta Yuliana, Dhea; Suryaningsum, Sri (Count : Journal of Accounting, Business and Management, 2024)
This study examines to analyze empirical evidence regarding financial and non-financial factors on the level of stock underpricing when carrying out Initial Public Offering (IPO) on the IDX for the period 2018-2023. The underpricing phenomenon occurs when the offer price on the Initial Market is smaller than the share price at the close of the first day. the variables used in this study are Return on Asset (ROA) as X1, Debt to Equity Ratio (DER) as X2, and underwriter reputation as X3, Company Size as X4, Company Age as X5, and Net Profit Margin (NPM) as X6 and Underpricing Level as Y. This study uses secondary data in the form of company prospectus reports obtained through the Indonesia Stock Exchange. The number of samples used amounted to 268 companies with a purposive sampling method. The analysis technique is multiple linear analysis with IBM SPSS Version 26. Based on the results of data analysis shows that Underwriter Reputation affects the Underpricing Level. While ROA, DER, Company Size, Company Age, and NPM have no effect.